1990
DOI: 10.2307/2409525
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Novelty and Atavism in the Semionotus Complex: Relaxed Selection During Colonization of an Expanding Lake

Abstract: Fishes of the genus Semionotus diversified in the rift lakes of eastern North America during the Mesozoic (Newark Supergroup). Like the well-known cichlid fishes of the African great lakes, diverse complexes of semionotids were apparently endemic to a number of different lakes. Semionotid fishes show considerable morphological diversity in body shape and in a modified row of scales termed "dorsal ridge scales." A number of distinct dorsal-ridge-scale patterns characterize groups of species from the Newark Supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In Great Britain it appears to occur at the top of the contorted interval interpreted as a seismite (Mayall 1983;Simms 2007), corresponding to the base of the 'initial' isotopic excursion of Hesselbo et al (2002) and within the 'dead zone' that marks the marine extinction level (Mander et al 2008 fig. Kozur & Weems (2007 also cite Bulbilimnadia sheni from the middle East Berlin Formation of the Hartford basin (Westfield Fish Bed), and the present authors have found this taxon in the exact homotaxial and time equivalent in the Newark basin, 'cycle P3' of McCune (1990) (Olsen 2010). 9) in the Newark basin, and in the Newark Supergroup in general, below the oldest basalt and above the E. olseni zone, and specifically between the grey shale marking the base of the Exeter Township Member of the Passaic Formation and the Orange Mountain Basalt, as discussed above.…”
Section: Conchostracan Biostratigraphysupporting
confidence: 51%
“…In Great Britain it appears to occur at the top of the contorted interval interpreted as a seismite (Mayall 1983;Simms 2007), corresponding to the base of the 'initial' isotopic excursion of Hesselbo et al (2002) and within the 'dead zone' that marks the marine extinction level (Mander et al 2008 fig. Kozur & Weems (2007 also cite Bulbilimnadia sheni from the middle East Berlin Formation of the Hartford basin (Westfield Fish Bed), and the present authors have found this taxon in the exact homotaxial and time equivalent in the Newark basin, 'cycle P3' of McCune (1990) (Olsen 2010). 9) in the Newark basin, and in the Newark Supergroup in general, below the oldest basalt and above the E. olseni zone, and specifically between the grey shale marking the base of the Exeter Township Member of the Passaic Formation and the Orange Mountain Basalt, as discussed above.…”
Section: Conchostracan Biostratigraphysupporting
confidence: 51%
“…The accumulation of species−richness calcu− lated for Ceratites is an order of magnitude lower than exam− ples of species−flocks of fishes (Greenwood 1981;McCune 1990McCune , 1996 and Cretaceous ammonites (Yacobucci 1999), but the radiation of Ceratites remains an important case of a radiation within a restricted area in the fossil record.…”
Section: Discussionmentioning
confidence: 90%
“…The cichlid flocks of the African Rift Lakes (Meyer 1993) and the radia− tion of Geospiza (Darwin's finches) on the Galapagos Is− lands are two exemplars of geographically restricted radia− tions among living taxa. McCune (1990McCune ( , 1996 provided convincing evidence that such events can be detected in the fossil record as far back as the Triassic among Semionotus fish in rift−basins.…”
Section: Introductionmentioning
confidence: 92%
“…"Pathomoplasy phylogenetically close to the or-tern" is meant in a statistical sense as a igin of major morphological innovations deviation from randomness in a way that (Riedl, 1978;Donoghue, 1989) or at the will be made precise below. The spatial patbase ofadaptive radiations (McCune, 1990). terns can assume many particular forms ( Fig.…”
mentioning
confidence: 99%